Dimensions Necessitated for Total Service Operations Management (TSOM) / Ardiana Mazwa Raudah Amir Abdullah... [et al.] - Amir Abdullah, Ardiana Mazwa Raudah; Abdullah, Firdaus; Voon, Boo Ho; Mathew, Vloreen Nity; Abg Mohar, Abg Hamizam (2014)
The service industry has played an increasingly significant role in many economies and is no different to the Malaysian C, contributing positively to the Gross Domestic Product (GDP), with a steady and consistence annual increase compared to the manufacturing sector. The growth of the Malaysian economy has also witness an increasingly aggressive competition among service providers in all different segments to survive and achieve competitive advantage. The increasing market dynamism has forced service providers to adapt to ensure survival. Failure to adapt will led to inability to sustain competitions and may affect survival. Vast studies in manufacturing areas have empirically indicated operational practices deployed have resulted in superior operational performances. As such operational practices has been commonly seen by service providers as a tools to achieve competitive advantage. Yet, developments and contributions in the field of operations management, since its origin, have been strongly influenced by manufacturing management practices, and as such its transferability to services management however calls for an in-depth study as services differ from the manufacturing of goods in a number of ways. Adding to this, there is relatively less study, that has collectively taken all these dimensions in a unified context and linking it to operations capability. In the context of service management, too much emphasis is being place on the topic of service quality leading to the development of SERVQUAL (Parasuraman, 1988), HEdPERF (Firdaus, 2006), PESPERF (Yildiz, 2009). Such frameworks are based on the customer's perceptions and expectations of both the service characteristics as well as the service provider, yet there is relatively less studies on the framework of service operations management.